1997
DOI: 10.1128/aem.63.4.1288-1297.1997
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of streptomycin-producing streptomycetes in Brazilian soils

Abstract: Actinomycetes were isolated from soybean rhizosphere soil collected at two field sites in Brazil. All the isolates were identified as Streptomyces species and were screened for streptomycin production and the presence of two genes, strA and strB1, known to be involved in streptomycin biosynthesis in Streptomyces griseus. Antibiotic resistance profiles were determined for 53 isolates from cultivated and uncultivated sites, and approximately half the strains were streptomycin resistant. Clustering by the unweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…Previous studies of subtropical soils planted with soybeans indicated a prevalence of S. griseus on streptomycin-containing isolation plates. Evidence for the prevalence of strA in community DNA extracted from the soil was also recovered [29]. In these soils the streptomycete populations were stimulated by liming, which was accompanied by an increased occurrence of streptomycin resistant Bradyrhizobium japonicum strains.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies of subtropical soils planted with soybeans indicated a prevalence of S. griseus on streptomycin-containing isolation plates. Evidence for the prevalence of strA in community DNA extracted from the soil was also recovered [29]. In these soils the streptomycete populations were stimulated by liming, which was accompanied by an increased occurrence of streptomycin resistant Bradyrhizobium japonicum strains.…”
Section: Discussionmentioning
confidence: 92%
“…The calcareous CW soil, with pH 8, supported high streptomycete populations as indicated from the total actinomycetes count. This environment favours actinomycete growth and previous studies have shown that liming soil resulted in increased Sm R streptomycetes [29]. It is not clear why more alkaline soil conditions should favour Sm R , however, limed soil had more bioavailable Sm [30] which may provide a competitive advantage for producers.…”
Section: Discussionmentioning
confidence: 99%
“…These soils are very peculiar, with a unique vegetation characteristic of the Brazilian Central Plateau. Studies about their microbial diversity are scarce, specially for actinomycetes (Huddleston et al 1997). As pointed out by Bull et al (1992), most of the diversity of the world is yet to be discovered, mainly in habitats with the characteristics of the cerrado.…”
Section: Resultsmentioning
confidence: 99%
“…No novel bands appeared in the unamended and amended soils at week 12. Band D6, which was also present during week 8 (as band C3), matched two genera of actinomycetes, Streptomyces bikiniensis (99% similar), a producer of and resistant to streptomycin [21], and Geodermatophilus sp. (97% similar), which is a strictly aerobic, chemoorganotrophic, and mesophilic bacterium [14], while sequences with band D4 matched 100% to Streptomyces cyaneus.…”
Section: Bacterial Identi¢cationmentioning
confidence: 89%